Integration of New Media and Prophetic Communication Enhanced for Zakah, Infāq, Ṣadaqah, and Waqf Fundraising: A Case Study of Baitulmaal Munzalan Indonesia - Rasiam, Rasiam; Umiyati, Umiyati; Habibullah, Habibullah; Syahrir, Dimas Kenn; Said, Muhammad (Journal of Islamic Law, 2023)
Recent developments in Islamic philanthropic practices have shifted from traditional to modern ways through the use of information technology. This article seeks to analyze how prophetic communication is integrated by Baitulmaal Munzalan Indonesia (BMI) in its use of new media to enhance Zakah, Infāq, Ṣadaqah, and Waqf (Ziswaf) fundraising. This research uses a qualitative method by conducting field work through primary and secondary data collection. Primary data were collected through observation and interviews with members of the executive board and managers of this institution, while secondary data were obtained by exploring its website and social media. We found that the BMI has been using a number of new media, both online media and social media, to build the trust of the Muslim community in charity. Millennials are recruited as agents to carry out all of the BMI’s carefully planned programs. Through its social media, the BMI uses prophetic communication by involving several well-known ustadz (preachers) on social media as ambassadors for Ziswaf fundraising. We argue that the transformation of new media that communicate religious messages and are supported by the millennial movement has become an ecosystem for collecting, managing and distributing Ziswaf funds in its latest practice.